Migration And Female Labor Market: Post-Border Opening Analysis 2023 In San José De Cúcuta - Tarazona, Edy Maribel Guerrero; Delgado, Marisol Maestre (Journal of Ecohumanism, 2024)
This study analyzes the impact of the reopening of the Colombia-Venezuela border in 2023 on the female labor market in San José de Cúcuta, a region characterized by high human mobility and structural inequalities. Through a quantitative, descriptive-correlational approach and a synthetic control model, indicators such as the female unemployment rate, labor force participation, and average income were examined. The results reveal a complex labor environment. After the reopening, female unemployment fluctuated between 10% and 15%, with an ATE of -0.054, while labor force participation reached 44.3%. However, labor informality (65%) and wage gaps persist, affecting both locals and migrants. Migrant women face additional barriers, such as a lack of educational certification and work experience, which hinder their access to formal employment. The synthetic control analysis concludes that, although the female unemployment rate tended to decline in 2023, it experienced a slight increase in 2024, remaining in double digits. Employment competition, exacerbated by migratory flows, has limited opportunities for women. It is concluded that the reopening has not improved their working conditions, highlighting the need for comprehensive policies to promote gender equity and socio-economic inclusion. Keywords: Migration, Female labor market, Gender inequality, Colombia-Venezuela border, Socioeconomic inclusion.